Impacto y análisis de las normas internacionales en el desarrollo de las funciones del revisor fiscal en Colombia (2018)
Historically, the public accountant role is necessary and fundamental for economic development of organizations, in Colombia to profesionals of public accounting were granted the capacity of exercise like “revisor fiscal”5 , figure that served like an State support for giving security for investors and other accounting and financial information users.In the last years the public accountant profession has been important changes in these regulation and focus, thanks to the changes driven for the harmonization of accountant language in the frame of International Financial Reporting Standards (IFRS), which will alow that the public accounting be more analytic and more participative in take decisions of organization.This paper makes an analysis of “revisor fiscal” functions in the frame of convergence to IFRS, and potentials and limitations of their activiti development in these context